Genetic versus environmental contributions to variation in seedling resprouting in Nothofagus obliqua - Aparicio, Alejandro Gabriel; Zuki, Sebastián Maximiliano; Azpilicueta, Maria Marta; Barbero, Fernando Alvaro; Pastorino, Mario Juan (Springer, 2018)
Resprouting is an almost universal functional trait in temperate angiosperms and confers persistence at an individual level after the loss of above-ground biomass. The importance of genetic versus environmental sources of intraspecific variation in resprouting traits is largely unknown. We conducted two genetic field trials, 400 m apart in altitude, in order to sequentially assess seedling resprouting in four environmentally contrasting Argentinean populations of Nothofagus obliqua Mirb. (Oerst). We also performed one nursery test to determine whether populations differed in early root/shoot biomass partition, a key trade-off affecting resprouting. Initial resprouting vigour and final survival were higher in our warmer test site, located 300 m below the core range of the species. The main contrasts between populations were found for pre-clipping seedling size and resprouting profusion, the latter trait showing a clear trade-off with resprouting vigour. Site × population interactions were due mainly to the behaviour of the highest altitude population, suggesting its divergent adaptive trajectory and higher plasticity for resprouting traits. Within populations, trait heritability was low, in general. Episodic frost, which may limit resprouting vigour and final success, had a lower incidence in the altitudinal and xeric limit populations. Overall, our work revealed genetic variation between populations of N. obliqua in traits that determine the success of seedling resprouting, probably associated with divergent selection. Low trait heritability suggests limited in situ micro-evolutionary capacities for resprouting traits under ongoing climate warming; phenotypic plasticity may play an important role in population persistence at the low positions of the elevation gradients N. obliqua currently inhabits.